Does the gender composition of sibships affect womens's educational attainment? - Hauser, Robert M. [Verfasser]; Kuo, Hsiang-Hui Daphne [Verfasser] (My University, 1998)
"data from the Panel Study of Income Dynamics, the November 1989 Current Population Survey, and the National Langitudinal Study of Women suggest that women with sisters may have completed less schooling than women without sisters. This hypothesis follows a long tradition of theories about the effects of siblling number and configuration. There is relatively weak evidence for this hypothesis in the analysis on which the findings are based. Analyses of the effects of sibling gender composition on educational attainment among cohorts of women in the Occupational Changes in a Generation Survey, the Survey of Income and Program Participation, and the National Survey of Families and Households offer no support for this hypothesis of for other related hypotheses about the effects of the gender composition of sibships." (author's abstract, IAB-Doku) Die Autoren untersuchen den Einfluss von Schwesternkonstellationen auf (schulische) Bildungsabschlüsse. (IAB)
Keywords: G 1.3.1 Bildungsangebot & -nachfrage; G 2.4.2 Lebenskonzepte, -stile, Werte; G 2.3.5 Wirtschaftsstrukturwandel; G 2.4.5 Gender Mainstreaming; I 2.3.2 Nordamerika; Bildungsabschluss; Familie; Struktur; Geschlechtsspezifische Faktoren; Geschlechterverteilung; USA